2002
DOI: 10.5194/angeo-20-1737-2002
|View full text |Cite
|
Sign up to set email alerts
|

The storm time central plasma sheet

Abstract: Abstract. The plasma sheet plays a key role during magnetic storms because it is the bottleneck through which large amounts of magnetic flux that have been eroded from the dayside magnetopause have to be returned to the dayside magnetosphere. Using about five years of Geotail data we studied the average properties of the near-and midtail central plasma sheet (CPS) in the 10-30 R E range during magnetic storms. The earthward flux transport rate is greatly enhanced during the storm main phase, but shows a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The difference in magnetotail variations between the two types of substorms is only in terms of size. The magnitude of variations in various parameters tends to be larger for storm time, as shown in the present and previous studies [ Baumjohann et al , 1996, 2004; Daglis et al , 1998; McPherron and Hsu , 2002; Schödel et al , 2002]: the north‐south magnetic field, the total pressure, the temperature, the electric field, and compositional change (O + ). To address the storm‐substorm relationship, it is important to understand quantitative differences in magnetotail variations between storm and nonstorm time substorms and furthermore whether or not the difference in each parameter is essential for the development of storms.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The difference in magnetotail variations between the two types of substorms is only in terms of size. The magnitude of variations in various parameters tends to be larger for storm time, as shown in the present and previous studies [ Baumjohann et al , 1996, 2004; Daglis et al , 1998; McPherron and Hsu , 2002; Schödel et al , 2002]: the north‐south magnetic field, the total pressure, the temperature, the electric field, and compositional change (O + ). To address the storm‐substorm relationship, it is important to understand quantitative differences in magnetotail variations between storm and nonstorm time substorms and furthermore whether or not the difference in each parameter is essential for the development of storms.…”
Section: Discussionsupporting
confidence: 82%
“…Figure 4 shows X ‐directional profiles of the total pressure itself ( P t ) at onset. The total pressure is higher in the entire tail throughout the interval (not shown) for storm time than for nonstorm time, as shown by McPherron and Hsu [2002] and Schödel et al [2002]. This suggests that energy is more accumulated in the magnetotail, and the cross‐tail current is more intense during storm time.…”
Section: Superposed Epoch Analysesmentioning
confidence: 88%
“…The close distance of NENL to Earth contradicts at first glance earlier spacecraft observations. According to spacecraft observations from, e.g., Geotail and Cluster the location of the NENL have typically been found at a distance between 20 to 30 R E downtail [ Nagai et al , 1998; Baumjohann et al , 1999; Baker et al , 2002; Schödel et al , 2002; Miyashita et al , 2003] during substorm conditions. In comparison, Siscoe and Crooker [1974] predicted this distance empirically to be between 10 R E and 30 R E during substorms based on a linear relation between the time rate of change of Dst and the reconnection electric field.…”
Section: Substorm Energy Budgetmentioning
confidence: 99%
“…Thus they concluded that there was no qualitative difference between the substorm types. Schoedel et al [2002] compared the average plasma moments in the plasma sheet during storm times and nonstorm times. They found enhanced rates of earthward flux transport during storm times in the 20–30 Re plasma sheet, and significantly reduced rates further in.…”
Section: Introductionmentioning
confidence: 99%